The Application of Character Values in Indonesian History: Contextual Approaches and Their Implementation to Strengthen Students' Character - Mira Puspita; Azmi Fitrisia (AL-ISHLAH: Jurnal Pendidikan, 2025)
History education holds strategic potential in shaping student character by integrating values essential to national identity, such as nationalism, integrity, tolerance, and empathy. However, recent revisions to Indonesian History learning materials have not sufficiently emphasized these character-building elements. This gap presents a challenge in transforming history education from mere knowledge transmission into a medium for character development. This study employed a qualitative approach using Critical Discourse Analysis (CDA). Data were collected through document analysis, in-depth interviews with educators, and classroom observations. The analysis focused on identifying discursive patterns in history teaching materials and the nature of educator-student interactions during lessons. The study revealed that current history materials lack consistent integration of character values. Educators often rely on traditional narratives that fail to engage students with contextual or ethical dimensions of historical events. Additionally, classroom practices rarely encourage reflective or empathetic discussions that could foster character development. These findings highlight the need to reframe history learning as a platform for character education. Strategies such as incorporating value-based narratives, promoting student-centered discussions, and aligning content with contemporary social issues are discussed. The study proposes a responsive pedagogical framework tailored to the challenges of globalization and evolving educational priorities. This research offers practical recommendations for enhancing Indonesian History curricula to better support character education. It contributes to the broader discourse on curriculum reform and underscores history’s role in shaping morally grounded and socially responsible citizens.